IMPACT OF THE MIS-TLIF TECHNIQUE ON THE SPINOPELVIC PARAMETERS OF PATIENTS WITH LUMBAR ARTHRODESIS - Cristiano Magalhães Menezes; Leonardo Fernandes Aguiar; André de Oliveira Arruda; Rodrigo Vieira Cardoso; Germano Senna Oliveira do Valle; Rodrigo Souza Lima; Mário Leite Bringel; Felipe Miranda Mendonça Fernandes; Joint Halley Guimbard Pérez (Coluna/Columna)
ABSTRACT Objective: To evaluate the influence of the MIS-TLIF technique on the spinopelvic parameters of patients submitted to lumbar arthrodesis up to three levels for the treatment of vertebral degenerative conditions without deformity. Methods: Retrospective radiographic evaluation of 52 patients submitted to the surgical treatment of lumbar arthrodesis using the MIS-TLIF technique in up to three levels. The spinopelvic parameters – pelvic incidence (PI), pelvic tilt(PT), lumbar lordosis (LL), segmental lordosis (Lseg), and the difference between lumbar lordosis and pelvic incidence (LL-PI mismatch) were analyzed in orthostatic lateral radiographs in the pre- and postoperative periods, with a minimum follow-up of 1 year. The patients were divided into three groups: PI <45°, PI between 45° and 55° and PI >55°. Results: Sixty-nine operated levels were evaluated in 15 patients with PI <45°, 19 with PI between 45° and 55° and 18 with PI >55°. The mean value of the pelvic incidence was 52.3° (± 11.5), lumbar lordosis 46.1° (pre)/45.6° (post); segmental lordosis 20.3° (pre)/20.6° (post); pelvic tilt 18.5° (pre)/18.2° (post); “mismatch” (PI-LL) 7° (pre)/ 6.6° (post), with no statistical difference among all parameters (p>0.05). Conclusions: The MIS-TLIF technique had no influence on postoperative spinopelvic parameters of patients undergoing lumbar arthrodesis surgery. Level of evidence: III. Retrospective comparative study.